Multiple sclerosis: current state - A. V. Peresedova; I. A. Zavalishin (Анналы клинической и экспериментальной неврологии, 2017)
Etiology of multiple sclerosis has both genetic and environmental components. The current conception is that multiple sclerosis pathogenesis comprises an initial inflammatory phase, followed by a phase of demyelination and last, a neurodegenerativephase. The mechanisms of inflammatory reactions, axonal lossand reparative changes have been discussed. There are two schemes of treatments: the escalating approach and the inductiontherapy. One of the main principles of disease modifying therapy of MS is treat-early approach. Results of interferons-b andglatiramer acetate comparison as first-line MS therapy havebeen described. The use immunosuppressive agents and futuredevelopments of MS therapy have been discussed.